THE INFLUENCE OF TALENT MANAGEMENT ON EMPLOYEE PERFORMANCE WITH EMPLOYEE INVOLVEMENT AS A MODERATING VARIABLE - Dikky Mooy; Teguh Setiawan Wibowo; Karyono Karyono; Muhammad Risal Tawil; Titin Titin (ITB AAS Indonesia Surakarta, 2024)
Abstract This research is quantitative research with an exploratory approach which uses a number of previous studies such as Talent Management, Employee Performance and Employee Involvment. The data used in this research was obtained from 300 Ms-Glow employees spread throughout Indonesia. These data were obtained from distributing a questionnaire containing 5 questions containing strongly agree, disagree, normal/average, disagree and strongly disagree. The result in this research show the Talent Management variable has a positive and significant relationship to Employee Performance because the P-Values value is positive and is below the 0.05 significance level, namely 0.022.. Apart from the above related to the hypothesis, researchers also believe that Employee Engagement is part of good Telelent Management. Therefore, Employee Engagement can influence Talent Management and can also influence Employee Performance. On this basis, the researcher assumes that it is also the second hypothesis in the research that the Employee Engagement variable can moderate the influence of the Talent Management variable on Employee Performance. The results of the second row of the third table of path coefficients show that the Employee Engagement variable can moderate the influence of the Talent Management variable on Employee Performance. This is because the P-Values value is positive and is below the significance level of 0.05, which is 0.000, which is more significant than direct testing. Therefore, the first and second hypotheses in this study can be accepted.